Endoscopic Submucosal Dissection for the Treatment of Superficial Epithelial Gastric Neoplasia in a Portuguese Centre - Costa, Rita Seara (2019)
The emergence of endoscopic submucosal dissection (ESD) made possible en bloc resection of neoplastic gastric lesions, regardless of lesion size, with reduced rates of complications and recurrence. This technique has become the preferred method for curative resection, instead of conventional endoscopic mucosal resection and surgery, when distant metastases have negligible risk. In Western countries experience with this technique has evolved quickly, with an increasing number of case series reported in the literature. This study aims to report the short- and long-term outcomes of ESD in gastric epithelial neoplastic lesions by a single operator in a Portuguese centre.